Health behaviour change among commercially sexually exploited Israeli youth and young adults in a multi‐module program - Preis, Heidi; Peled, Einat; Shilo, Guy (Health & social care in the community, 2020)
Commercially sexually exploited youth and young adults (hereafter CSEY) are at high risk for various health adversities, but little is known about interventions that can improve their health outcomes. This study reports changes in health behaviours—positive health behaviours, drug use and risky sexual behaviour—in the first stages of treatment of 122 participants in a comprehensive multi‐module program for CSEY in Israel. Data included sociodemographic and background information upon program entry, monthly reports on the treatment the participants received and their status. Data were collected monthly through online questionnaires completed by case managers for each of the CSEY in their care. A three‐part analytic strategy assessed changes in repeated measures over time and their contributors. Latent class analysis helped identify differential trajectories of change over time among different participant groups. Findings showed overall significant decrease in risky sexual behaviours and improvement in positive health behaviours among certain CSEY groups. Participants with higher levels of health‐risk situations and behaviour at program entry (e.g. more victimisation, less residential safety) were more likely to show improvement in health behaviours during intervention, but less likely to change their moderately risky sexual behaviours. Program participants with high levels of drug use did not show improvement in drug use patterns over time. This study demonstrates that a comprehensive multi‐module intervention for CSEY can significantly improve health behaviour outcomes among serviced CSEY, and highlights the value of person‐oriented care, and of research that can detect vulnerable subpopulations within CSEY who require uniquely tailored interventions. Personalising treatment to specific differential needs of CSEY, coupled with early detection and intervention, can improve program outcomes. Further research is needed to understand contributors to change and changes in subsequent health outcomes.